Testing Bromocriptine Dose Necessary For Suppression of Lactation in Rats: Morphological Study - Al-Khalisi, maan; Al-Khateeb, Huda (Iraqi National Journal of Nursing Specialties, 2005)
Abstract: Objectives: The lowest dose of bromocriptine, necessary for suppression of lactation in rats, was estimated in this investigation. Methodology: Fifty healthy lactating rats were treated with different doses of bromocriptine. Cessation of lactation was assessed clinically and histologically. Results: Revealed that the lowest dose capable of lactation suppression is 4 mg bromocriptine / kg body wt. / day. It is very important to know the exact dose, which can suppress lactation in rats because these laboratory animals are commonly employed in experiments concerning this topic. Key words: Bromociptine, Cessation of Lactation